Development of brainstem 5‐HT1A receptor‐binding sites in serotonin‐deficient mice. (10th June 2013) - Massey, Caitlin A.; Kim, Gloria; Corcoran, Andrea E.; Haynes, Robin L.; Paterson, David S.; Cummings, Kevin J.; Dymecki, Susan M.; Richerson, George B.; Nattie, Eugene E.; Kinney, Hannah C.; Commons, Kathryn G.
Abstract: The sudden infant death syndrome is associated with a reduction in brainstem serotonin 5‐hydroxytryptamine (5‐HT) and 5‐HT1A receptor binding, yet it is unknown if and how these findings are linked. In this study, we used quantitative tissue autoradiography to determine if post‐natal development of brainstem 5‐HT1A receptors is altered in two mouse models where the development of 5‐HT neurons is defective, the Lmx1b f/f/p, and the Pet‐1 −/− mouse. 5‐HT1A receptor agonist‐binding sites were examined in both 5‐HT‐source nuclei (autoreceptors) and in sites that receive 5‐HT innervation (heteroreceptors). In control mice between post‐natal day (P) 3 and 10, 5‐HT1A receptor binding increased in several brainstem sites; by P25, there were region‐specific increases and decreases, refining the overall binding pattern. In the Lmx1b f/f/p and Pet‐1 −/− mice, 5‐HT1A ‐autoreceptor binding was significantly lower than in control mice at P3, and remained low at P10 and P25. In contrast, 5‐HT1A heteroreceptor levels were comparable between control and 5‐HT‐deficient mice. These data define the post‐natal development of 5‐HT1A ‐receptor binding in the mouse brainstem. Furthermore, the data suggest that 5‐HT1A ‐heteroreceptor deficits detected in sudden infant death syndrome are not a direct consequence of a 5‐HT neuron dysfunction nor reduced brain 5‐HT levels. To elucidate the developmental relationship between serotonin (5‐HT) levels and 5‐HT1A receptors in the brainstem, we examined 5‐HT1A binding in two 5‐HT‐deficient mouse models. In nuclei containing 5‐HT neurons, 5‐HT1A binding was decreased (autoreceptors), while binding was maintained in projection sites (heteroreceptors). Thus, brainstem 5‐HT1A ‐heteroreceptor‐binding sites do not appear developmentally sensitive to reduced brain 5‐HT levels. Abstract : To elucidate the developmental relationship between serotonin (5‐HT) levels and 5‐HT1A receptors in the brainstem, we examined 5‐HT1A binding in two 5‐HT‐deficient mouse models. In nuclei containing 5‐HT neurons, 5‐HT1A binding was decreased (autoreceptors), while binding was maintained in projection sites (heteroreceptors). Thus, brainstem 5‐HT1A ‐heteroreceptor‐binding sites do not appear developmentally sensitive to reduced brain 5‐HT levels.